Theodor Körner, az NDK politikai mítosza: A német nacionalizmus hagyománya az NDK irodalmában - Kovács, Kálmán (Studia Litteraria, 2018)
The biographic novels about Theodor Körner accurately demonstrate the significant paradigm shifts in East Germany’s memory politics. Before 1949, the nationalistic tradition was rejected even in the area under Soviet occupation, nevertheless it became a central element of East Germany’s ideology after the turn of 1952. One must add, that it was not picked up in its original form, but adapted to the requirements of the present. The Körner novels reveal the main characteristics of this transformed nationalism. The political changes of the seventies generated a turn of cultural policy as well. The particularities of this new paradigm are reflected in Ulrich Völkel’s novel about Theodor Körner. The recycled myth of Körner paints a picture of East Germany which we came to know during the last decade of its existence.